Торгово-военные пути скифского времени и «татарские дороги» на южном прикордонье Правобережной Лесостепи - Полтавец, В.И.; Бессонова, С.С. (Археологія і давня історія України, 2015)
В статье приведены сведения о двух ключевых территориях на торгово-военных путях скифского и козацкого периодов, проходивших через низовья Тясмина и бассейн Великой Выси. В писемних джерелах XVI—XVIII ст. відомі «татарські шляхи» в Діпровському Правобережжі, які
поєднували Дике поле з Лісостепом і проходили
через перевози на прикордонних річках. Це Крилов/Новогеоргієвськ в пониззі Тясмину і Златополь/
Новомиргород на Великій Висі. Ці міста згадуються переважно у зв'язку з воєнними набігами і руйнуваннями. Безсумнівним є важливе стратегічне і торговельне (особливо у XVIII ст.) значення цих поселень. Подібну ситуацію можна припускати й для
скіфського періоду. Це підтверджують дружинні
курганні могильники поблизу с. Журовка в басейні
Великої Висі і Світловодський могильник на р. Цибульник (притока Тясмину) неподалік Дніпра. За
скіфських часів, до кінця V — початку IV ст. до н. е.,
шляхи вздовж Дніпра мали насамперед стратегічне значення, на відміну від переважно торгівельних шляхів в басейні Великої Висі. В козацькі часи, коли існували розвинені річкова і морська торгівля,
шляхи вздовж Дніпра мали першорядне стратегічне значення. До того ж, тут знаходилися головні історичні осередки запорожців — від Києва і Канева до Каменської Січі. Всі вони виникли поряд з великими переправами, що підкреслює значення торгівлі
в житті запорожців. Суттєве значення мали також природні багатства в районі переправ, в тому числі
сприятливі умови для розвиненого скотарства і особливо конярства. In written sources of XVI—XVIII centuries there are
known «Tatar roads» on the right bank of the Dnipro
river that connected Wild Field with forest-steppe and
passed through the border rivers crossing. These are
Krylov / Novogeorgiyevsk in the Lower Tyasmyn and
Zlatopol / Novomyrhorod on the Great Vys river. The
cities are mentioned mainly in connection with military
invasions and devastation. Undoubtedly there is an
important strategic and trade [especially in the XVIII
century] value of these settlements. A similar situation
can be assumed for the Scythian period. That fact can
be confirmed by the fighting squad burial mounds near
the village Zhurovka in the basin of the Great Vys and
Svetlovodsky cemetery on the Tsybulnik river [inflow
of Tyasmyn river] not far from the Dnipro river. In the
Scythian time, until the end of the V — the beginning of the IV centuries BC, the roads along the Dnipro had
mostly military significance, in contrast to the mainly commercial roads in the Great Vys basin. In Cossack
times, when there were developed river and maritime trade, the road along the Dnipro had primary strategic
importance. Besides, here were located the main historical centers of the Zaporozhye Cossacks — starting
from Kiev and Kanev to Kamenskaya Sech. All of them were formed around major river crossings, which underline
the major role of trading in the life of the Cossacks. Not less important role played natural resources
in the area of the crossings, including good conditions for developed cattle-breeding and especially horsebreeding.